Pola Saluran Pemasaran Agroindustri Kopi Bubuk Di Desa Muara Madras Kecamatan Jangkat Kabupaten Merangin - Kurniasih, Siti; Effran, Endy (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
This study aims 1) To describe the marketing location of coffee powder in Muara Madras Village in Merangin Regency and outside Merangin Regency. 2) To find out the pattern of marketing channels for ground coffee agroindustry in Muara Madras Village, Jangkat District, Merangin Regency. 3) To find out the marketing efficiency channel for coffee powder in Muara Madras Village, Jangkat District, Merangin Regency. This research was conducted from 21 June 2021 to 02 July 2021 with primary and secondary data sources. The analytical method used in this research is descriptive qualitative and quantitative analysis with a sample of 3 agroindustry 19 traders. The results showed that 1) The distribution of marketing locations for ground coffee in Muara Madras Village from the total distribution of 70 percent of ground coffee marketing was in Merangin Regency, namely Bangko District and sales out of Merangin Regency, 2) Marketing of ground coffee in Muara Madras Village consisted of 3 marketing channel patterns, namely: (I) agroindustry - final consumers, (II) agroindustry - sub-district retailers - final consumers, (III) agroindustry - village retailers - final consumers. 3) Based on the marketing efficiency indicators with the marketing margin approach, the technical marketing efficiency index (IET), and the economic efficiency index (IEE) it has been explained that of the three marketing channel patterns, agro-industry I (agro-industry – end consumer) is more efficient in terms of the margin of the marketing pattern. I am more efficient because there is no price difference between agro-industry and end consumers and based on marketing efficiency, technical efficiency index (IET), and economic efficiency index (IEE) my marketing channel pattern is more efficient than other marketing channel patterns.Keywords: Marketing Distribution, Marketing Channel Pattern, Marketing Efficiency, Ground Coffee